CRISPR/Cas9: A Review on Genome Editing Tool - Sulabh, Sourabh; Bayan, Jyotishree; Kumar, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Throughout the history of recombinant DNA technology various tools have been used for manipulating the genome of an organism. Recent discoveries have led to novel insights into the world of endonucleases which can guide researchers to achieve the skill of editing genome in an efficient and easy way. CRISPR (Clustered Regularly Interspaced Short Palindromic Repeat)/ Cas9 system is among the newest and most effective members of genome editing tool and has been accepted by discoverers around the world as one of the most precise method of targeting and removal of a genome sequence and further utilization of other techniques to even incorporate a gene of interest in the same position in order to develop a transgenic organism. The applicability in reverse genetics studies, animal model experiments and also in curing diseases caused by viruses like HIV makes CRISPR/Cas9 system a highly desirable technique with the ability to achieve quick plausible outcomes.
Keywords: CRISPR/Cas9; endonuclease; Transgenesis